Urgensi Keterlibatan Penutur Asli dalam Penulisan Buku Ajar Bahasa Arab: Studi Pedagogik - Yulia Yuliani, Sri; Ali, Mad (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
Arabic textbooks play an important role in language learning, yet they often face challenges related to language authenticity and cultural relevance, especially in the context of learning in Indonesia. A key issue that often arises is the use of language that is stiff or does not reflect everyday conversation, as well as the lack of an introduction to the cultural context underlying the use of the language. Therefore, this research aims to analyze the importance of involving native speakers in the development of Arabic textbooks, as well as the impact of native speaker involvement on the authenticity of language, cultural relevance, and pedagogical effectiveness. The research method used in this study is a literature review, analyzing several Arabic textbooks that involve native speakers and those that do not, comparing the advantages and disadvantages of each. The results of the study show that textbooks involving native speakers offer more authentic language, stronger cultural relevance, and higher pedagogical effectiveness. These textbooks facilitate students' understanding of Arabic in a more in-depth and real cultural context. In contrast, textbooks that do not involve native speakers tend to be more structured and theoretical but lack the introduction of language used in everyday social life in the Arab world. The implications of this research highlight the importance of collaboration between native speakers, language experts, and educators in the development of Arabic textbooks. This collaboration aims to create instructional materials that not only teach grammar but also introduce the use of language in socially and culturally relevant contexts. The involvement of native speakers is crucial to improving the quality of Arabic language learning in Indonesia by introducing more authentic and contextual language